PERANCANGAN SISTEM INFORMASI SCHEDULE SHIFTING BERBASIS WEB Pada PT.KATA CIPTA MAKMUR - Ibrahim Aditama (2023)
Management procedures regarding scheduling shift work by a company or agency if not properly managed will result in the appearance of a complicated problem, especially if the company does not have optimal management in the process of applying for the scheduled shift work by utilizing human resources and available time. In this case study, PT. Kata Cipta Makmur in managing shift work, every day human resources send shift work to each employee through WhatsApp. Often uncertain scheduling, unbalanced scheduling and not having optimal confirmation or coordination, of course, will greatly affect the quality of working hours, the length of verification if there is a change in shift employee work and the submission of employees on leave that must be confirmed through WhatsApp first. Therefore, to minimize the obstacles in the scheduling management procedure shift work, then we need an information system that can provide scheduling information shift work. Schedule Shifting is included in an information-based system web which can be accessed on a platform anywhere connected to the internet network. By using the PIECES method to analyze the problem and apply the method System Development Life Cycle (SDLC) Waterfall as a development method software, using the PHP programming language with framework Laravel and MySQL for a database. The expected results in this study are the creation of a system that can facilitate managing scheduling shift work at PT. Kata Cipta Makmur.